Design and Development of Pipeline Inspection System - A. Ghani, Aslam (Universiti Teknologi PETRONAS, 2017)
Maintaining the pipeline integrity is very important in petroleum industry. Regular pipeline inspection is normally conducted. Pipeline Inspection Gauge (PIG) is used for internal inspection of the pipeline should there be any deformities and appropriate action plan need to be developed to prevent further deterioration or catastrophe. The PIG is an industrial device that moves by the driving force of the product flow inside the pipeline for detection of pipeline faults. Data analysis is conducted from the resulted information obtained after executing the in-line inspection. In this project, a PIG prototype equipped with Arduino based components is built to represent the actual industrial pipeline inspection system. The engineering concept is designed. The data of the colour tapes, distance, speed and shifted angle of the prototype are collected and validated. Colour sensors, rotary encoder, gyroscope and accelerometer are selected as sensing mechanism of the system. The data are stored in a memory card to be processed by the MATLAB for final analysis.